Digital Marketing Sebagai Strategi Komunikasi Pemasaran Rayyan Aqiqah Dalam Menjangkau Target Pasar - Arfan Aulia Rachman (Prodi Manajemen Dakwah STAIN Mandailing Natal, 2023)
Entering the era of marketing 4.0, marketing methods have shifted or transformed from traditional/conventional ways (offline) to electronic or digital ways (online), namely marketing methods using digital devices, namely websites and social media. This concept has begun to be applied by Aqiqah and food catering business actors in the city of Medan, namely Rayyan Aqiqah in marketing their service products anytime (real-time) and anywhere if connected to interconnection networking (internet). The problems raised, namely:. How is the digital marketing as strategy Rayyan Aqiqah's to reach its target market. This study uses a qualitative descriptive research with a phenomenological approach regarding digital marketing as a marketing communication strategy for an Rayyan Aqiqah in reaching the target market, then analyzed by data reduction, data presentation, and drawing conclusions. While the theory used in this research is the theory of integrated marketing communication strategy, Digital marketing strategy element Digital Comersialitation 4C Thomas Joseph theory, and marketing communication digital strategy AISAS model Dentsu theory. The results of this study explain that the Digital Marketing concept implemented by business people, namely Rayyan Aqiqah has succeeded in promoting, marketing and obtaining a more massive target market, namely prospective consumers to use service and product service in digital media and are able to maintain bussiness continuity against bussiness competitors kind.